Ocorrência de Acrocinus longimanus (Linnaeus) (Coleoptera: Cerambycidae) em área urbana, Nordeste do Brasil - Santos, Wellington Emanuel dos; Pereira-Colavite, Alessandre (EntomoBrasilis, 2017)
Resumo. Uma fêmea de Acrocinus longimanus (Linnaeus) foi coletada em perímetro urbano em Caruaru, Pernambuco, Brasil, sendo o primeiro registro da espécie em área verde urbana. Discussões sobre esse tipo de refúgio para a espécie também são apresentadas. Occurrence of Acrocinus longimanus (Linnaeus) (Coleoptera: Cerambycidae) in urban area, Northeastern Brazil Abstract. A single female of Acrocinus longimanus (Linnaeus) was collected in urban area in Caruaru, State of Pernambuco, Brazil, being the first record of the species in a novel ecosystem. Considerations about this kind of refuge for the species are also presented.